Representation matters: (re)articulating collective identities in a postcolonal world - Hoffmann, Anette; Peeren, Esther (Thamyris intersecting: place, sex, and race 1570-7253, 2010)
In the twenty-first century, the terms "representation" and "identity" seem to have gone out of fashion. The essays collected here, however, seek to demonstrate the extent to which they continue to matter in the social, political and cultural strug.